2009
DOI: 10.2174/157489009787259982
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Variability Analysis at Coronary Artery Disease and Angina Pectoris

Abstract: The purpose of this study was to present results of special examination and prospective observation of patients with coronary artery disease (CAD) and angina pectoris (AP) in practical cardiology. Except standard cardiological methods, we used high-resolution rhythmocardiography and apparatus-program complex for registration and analysis of the heart rate variability. There was an evaluation of the autonomic and humoral-metabolic regulative influences on pacemaker activity of the heart sinus node in 273 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…50,51 Although specific studies linking HRV with the risk of cardiovascular disease in patients with SLE have not been performed, it is unlikely that the finding that HRV measures may assist in the management of coronary artery disease in other patient populations would not also be true in SLE, as it has been shown that impaired functioning of the ANS is a negative prognostic factor in patients with acute coronary syndromes and is associated with increased cardiovascular risk. 52 Thus HRV can potentially be used to assess the severity of autonomic dysfunction in SLE patients and studies of changes in HRV with interventions may lead to ways to decrease potential cardiovascular risk in SLE. As a result, HRV assessment may prove to be useful in clinical practice regarding the care of patients with SLE.…”
Section: Discussionmentioning
confidence: 99%
“…50,51 Although specific studies linking HRV with the risk of cardiovascular disease in patients with SLE have not been performed, it is unlikely that the finding that HRV measures may assist in the management of coronary artery disease in other patient populations would not also be true in SLE, as it has been shown that impaired functioning of the ANS is a negative prognostic factor in patients with acute coronary syndromes and is associated with increased cardiovascular risk. 52 Thus HRV can potentially be used to assess the severity of autonomic dysfunction in SLE patients and studies of changes in HRV with interventions may lead to ways to decrease potential cardiovascular risk in SLE. As a result, HRV assessment may prove to be useful in clinical practice regarding the care of patients with SLE.…”
Section: Discussionmentioning
confidence: 99%
“…3 Patients with SCAD may experience HRV alteration due to increased sympathetic activities. 4 HRV measurements have different time intervals; short-term HRV (5-10 minutes) is similar to long term HRV (24 hours) in terms of risk stratification for ischemic heart diseases.…”
Section: Introductionmentioning
confidence: 99%